Energy efficiency optimization study of sub-connected ARIS-assisted ISAC system over millimeter wave channels - WU Xiangkai; YUE Dianwu; YUAN Meng; XU Miao; YANG Jianing (Dianxin kexue)
In order to solve the problems of large energy consumption, and poor performance gain of RIS in the traditional reconfigurable intelligent surface (RIS)-assisted integrated sensing and communication (ISAC) system, the sub-connected active reconfigurable intelligent surface (ARIS) was considered to be introduced into the ISAC system. The system energy efficiency was maximized by optimizing the beamform for dual-function base station, the phase shift matrix of sub-connected ARIS and the vector of amplification factors for sub-connected ARIS under the user’s minimum signal to interference plus noise ratio and the constraint of radar detection power. An algorithm based on fractional programming (FP) theory, alternating optimization (AO) technique, and successive convex approximation (SCA) technique was proposed to deal with the non-convex problem. The simulation results show that the algorithm has good convergence and the sub-connected ARIS-assisted ISAC system can significantly improve the energy efficiency of the system compared to the fully connected ARIS-assisted ISAC system.